# 99 questions/Solutions/17

### From HaskellWiki

(*) Split a list into two parts; the length of the first part is given.

Do not use any predefined predicates.

Solution usingtake

drop

split xs n = (take n xs, drop n xs)

splitAt

split = flip splitAt

But these should clearly be considered "predefined predicates". Alternatively, we have the following recursive solution:

split :: [a] -> Int -> ([a], [a]) split [] _ = ([], []) split l@(x : xs) n | n > 0 = (x : ys, zs) | otherwise = ([], l) where (ys,zs) = split xs (n - 1)

The same solution as above written more cleanly:

split :: [a] -> Int -> ([a], [a]) split (x:xs) n | n > 0 = let (f,l) = split xs (n-1) in (x : f, l) split xs _ = ([], xs)

Or (ab)using the "&&&" arrow operator for tuples:

split :: [a] -> Int -> ([a], [a]) split (x:xs) n | n > 0 = (:) x . fst &&& snd $ split xs (n - 1) split xs _ = ([], xs)

A similar solution using foldl:

split :: [a] -> Int -> ([a], [a]) split [] _ = ([], []) split list n | n < 0 = (list, []) | otherwise = (first output, second output) where output = foldl (\acc e -> if third acc > 0 then (first acc ++ [e], second acc, third acc - 1) else (first acc, second acc ++ [e], third acc)) ([], [], n) list

Note that for the above code to work you must define your own first, second, and third functions for tuples containing three elements like so:

first :: (a, b, c) -> a first (x, _, _) = x second :: (a, b, c) -> b second (_, y, _) = y third :: (a, b, c) -> c third (_, _, z) = z

Another foldl solution without defining tuple extractors:

split :: [a] -> Int -> ([a],[a]) split lst n = snd $ foldl helper (0,([],[])) lst where helper (i,(left,right)) x = if i >= n then (i+1,(left,right++[x])) else (i+1,(left++[x],right))